Sex differences in circulating inflammatory mediators as a function of substance use disorder. (1st April 2021) - May, April C.; Burrows, Kaiping; Figueroa-Hall, Leandra K.; Kirlic, Namik; White, Evan J.; Smith, Ryan; Ekhtiari, Hamed; Paulus, Martin P.; Savitz, Jonathan; Stewart, Jennifer L.; ,
Highlights: Peripheral inflammation appears to differ as a function of anxiety/depression. Inflammation levels in comorbid depression/anxiety and SUD are unknown. In females, higher interleukin 8 and 10 levels were linked to presence of SUD. In females, higher C-reactive protein levels were linked to absence of SUD. Across sexes, C-reactive protein and interleukin 6 were positively correlated. Abstract: Background: Substance use disorders (SUD) with comorbid depression and anxiety are linked to poor treatment outcome and relapse. Although some depressed individuals exhibit elevated blood-based inflammation (interleukin-6 [IL-6] and C reactive protein [CRP]), few studies have examined whether the presence of SUD exacerbates inflammation. Methods: Treatment-seeking individuals with major depressive disorder (MDD), anxiety disorders, and/or SUD ( N = 160; 80 % with MDD) recruited into the Tulsa 1000 study provided blood samples, participated in clinical interviews, and completed a questionnaire battery querying symptoms of current psychopathology and emotional processing. Analyses followed a multistep process. First, groups were created on the presence versus absence of 1+ lifetime SUD diagnoses: SUD+ (37 F, 43 M) and SUD- (60 F, 20 M). Second, a principal component analysis (PCA) of questionnaire data resulted in two factors, one indexing negative emotionality/withdrawal motivation and one measuring positive emotionality/approach motivation. Third, SUD groups, extracted PCA factors, and nuisance covariates (age, body mass index [BMI], nicotine use, psychotropic medication [and hormone/contraception use in females]) were entered as simultaneous predictors of blood-based inflammation (IL-6, IL-8, IL-10, tumor necrosis factor-α, and CRP). Results: Within females, SUD + exhibited higher IL-8 and IL-10 but lower CRP levels than SUD-. In contrast, SUD was not associated with biomarker levels in males. Across sexes, higher BMI was linked to higher IL-6 and CRP levels, and within the five biomarkers, IL-6 and CRP shared the most variance. Conclusion: These findings point to sex-specific inflammatory profiles as a function of SUD that may provide new targets for intervention.